Identification and abundance of brachuyurans (true crabs) in bragy. Luciente 1, Bolinao, Pangasinan - Perez, Cayetano II P. 4 0 16; 5 (2006)
u
Thesis: (B.S. Biology)-Pamantasan ng Lungsod ng Maynila, 2006.
Keywords: 2 -- 0; 6; 20; 20; 2